2018
DOI: 10.1161/strokeaha.117.018707
|View full text |Cite
|
Sign up to set email alerts
|

Second-Generation Hydrogel Coils for the Endovascular Treatment of Intracranial Aneurysms

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 17 publications
3
42
0
Order By: Relevance
“…The higher packing density of HydroCoils seems to be translated into a lower reintervention rate compared with first-generation coils. 6 With a total mortality rate of 0.6% directly after discharge and 2.7% in long-term follow-up, our results are in the range of published outcomes. 7 In direct comparison with surgical clipping, the mortality rate after the endovascular technique was at least equal to recent published data (1.9%-2.0%).…”
Section: Comparison Between Surgical Clipping and Endovascular Techniquesupporting
confidence: 56%
“…The higher packing density of HydroCoils seems to be translated into a lower reintervention rate compared with first-generation coils. 6 With a total mortality rate of 0.6% directly after discharge and 2.7% in long-term follow-up, our results are in the range of published outcomes. 7 In direct comparison with surgical clipping, the mortality rate after the endovascular technique was at least equal to recent published data (1.9%-2.0%).…”
Section: Comparison Between Surgical Clipping and Endovascular Techniquesupporting
confidence: 56%
“…In Europe, the German-French Randomized Endovascular Aneurysm Trial (GREAT) showed that in a group of 484 patients (226 patients treated with hydrogel and 230 patients treated with bare platinum), 19.9% of patients treated with hydrogel had unfavourable outcomes such as aneurysm recurrence, retreatment, mRS (modified Rankin Scale) of 3–5 and death as compared with 28.7% of patients treated with bare platinum. The authors recommended the use of second-generation hydrogel coils 6. In the USA, a similar trial was conducted, called the New Generation Hydrogel Endovascular Aneurysm Treatment (HEAT) Trial, which examined aneurysm recurrence within 18 months post-treatment between patients who were treated with the second-generation HydroCoil Embolic System (HES) and patients treated with the traditional platinum coils.…”
Section: Advances In Coil Propertiesmentioning
confidence: 99%
“…Devices to augment coil embolisation now include balloon-assist techniques and intracranial stents to increase coil packing and parent artery patency, as well as reduce the risk of coil herniation 5. Significant changes in coil properties have also been made to increase the aneurysm occlusion rates 6…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Poncyljusz’s RCT concluded that hydrogel coils were equally as effective as bare platinum coils [ 17 ]. Later, the second-generation hydrogel (Hydrosoft, HydroFrame[3D], MicroVention, Inc) was developed, which was softer, contained less hydrogel, and expanded slower than the first-generation one [ 19 ]. In 2018, GREAT(German-French Randomized Endovascular Aneurysm Trial) was established, and some researchers found that compared to bare platinum coils, hydrogel coils decrease the rate of unfavorable outcome events, recurrence, retreatment, morbidity mortality, and need for retreatment in small- and medium-sized intracranial aneurysms [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%